Mechanics Float for Cal Poly's Decennial Celebration - Frank Aston::::::photographer::: (1913)
Mechanics float made for Cal Poly's Decennial Celebration. Float is a horse-drawn wagon laden with machinery, forge equipment, and display of electrical apparatus and forge products. 4 students. Published in Bulletin (March 1915)